2018
DOI: 10.37358/rc.18.9.6566
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Diabetes. A model of complex thinking applied in medicine

Abstract: Since their first mention, almost 60 years ago, there were a plethora of articles about oxidative stress and antioxidants, published in a wide range of journals (biochemistry, cell physiology, molecular biology or environmental biology). Also, in the last decade the definition of oxidative stress (OS) undergone different changes, and currently OS is seen as a disruption of redox signalling and control. This review aims to offer the perspective of Complexity Theory on antioxidants framework, and diabetes diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
0
8
1
Order By: Relevance
“…The correlations between diabetes and glaucoma are controversial. Some studies have found diabetes to be a risk factor in glaucoma (42)(43)(44)(45)(46), and others find no correlation or even a negative correlation (47). In the present study, we found no correlation between these two frequent encountered pathologies, but only diabetic patients without diabetic retinopathy were included.…”
Section: Diastolic Hypotension (Dips)contrasting
confidence: 65%
See 1 more Smart Citation
“…The correlations between diabetes and glaucoma are controversial. Some studies have found diabetes to be a risk factor in glaucoma (42)(43)(44)(45)(46), and others find no correlation or even a negative correlation (47). In the present study, we found no correlation between these two frequent encountered pathologies, but only diabetic patients without diabetic retinopathy were included.…”
Section: Diastolic Hypotension (Dips)contrasting
confidence: 65%
“…In the present study, we found no correlation between these two frequent encountered pathologies, but only diabetic patients without diabetic retinopathy were included. Diabetic microcirculation impairment leads to retinal fiber layer damage by multiple pathological pathways: Oxidative stress, increased levels of retinal inflammation biomarkers and disruption of vasculo-retinal barrier (42,43,46).…”
Section: Diastolic Hypotension (Dips)mentioning
confidence: 99%
“…According to the type of glucose disturbance, 16 patients had type 1 diabetes, and 123 had type 2 dyabetes, the rest having a genetic predisposition and occasionally increased glucose levels in the serum. [28] Inflammatory bowel diseases are also known to be significant risk factors, especially after 10-15 years of disease progression, the risk being bigger in Ulcerative Colitis than in Crohn's Disease. In our study, almost 8% of patients (60 patients) had a long history of IBDs.…”
Section: Resultsmentioning
confidence: 99%
“…These aspects could be of also correlated to some degree to our group latest interests in combinations that might exist between smoking status, exercise performing and oxidative stress status modifications [30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%